2017
DOI: 10.1038/s41598-017-03599-8
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant telomere length and mitochondrial DNA copy number in suicide completers

Abstract: Short telomere length (TL) occurs in individuals under psychological stress, and with various psychiatric diseases. Recent studies have also reported mitochondrial DNA copy number (mtDNAcn) alterations under several neuropsychiatric conditions. However, no study has examined whether aberrant TL or mtDNAcn occur in completed suicide, one of the most serious outcomes of mental illnesses. TL and mtDNAcn in post-mortem samples from 528 suicide completers without severe physical illness (508 peripheral bloods; 20 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 69 publications
3
33
0
Order By: Relevance
“…This study was approved by the Ethical Committee for Genetic Studies of the Kobe University Graduate School of Medicine. Subject selection and sample preparation were performed as previously described [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was approved by the Ethical Committee for Genetic Studies of the Kobe University Graduate School of Medicine. Subject selection and sample preparation were performed as previously described [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Suicide is a significant public health problem worldwide with approximately 1 million suicides each year. Emerging evidence from genetic studies suggests an underlying genetic pathophysiology in suicidal behavior in people with severe stress or mental disorders [ 1 , 2 ]. In most countries, men have a much higher rate of completed suicide compared to women as well as greater lethality of the suicide method [ 3 5 ], although the pathophysiology of this sex difference remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we may not be observing the right tissue for lasting molecular changes in Holocaust survivors. While an increase of mtDNA due to chronic stress was shown in multiple tissues including saliva, blood and liver in animal models (Cai et al, 2015b), a post-mortem study on suicide completers showed opposite changes in mtDNA levels in blood and dorso-lateral prefrontal cortex (Otsuka et al, 2017). As such, a lack mtDNA copy number difference between Holocaust survivors and controls in blood cells with rapid turnovers does not exclude lasting changes in mtDNA copy number in other tissues that may have important consequences on health and disease.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in a recent study, early-life experiences of adversity and lifetime psychopathology were found to be associated with higher mtDNA copy number ( P < 0.001) [ 41 ]. Similarly, Otsuka et al [ 42 ] reported that mtDNA copy number was significantly higher among individuals who committed suicide than in controls.…”
Section: Discussionmentioning
confidence: 97%